Realizing a Child-Friendly School Environment: An Implementation Study at SMP Negeri 15 Yogyakarta - Anna Raisha Yasmine (Spektrum Analisis Kebijakan Pendidikan, 2025)
This research aims to 1) Describe the implementation of the Child Friendly School (SRA) program at SMP Negeri 15 Yogyakarta; 2) To identify the supporting and inhibiting factors in the implementation of the Child-Friendly School (SRA) program at SMP Negeri 15 Yogyakarta. This research uses a descriptive qualitative approach with data analysis techniques used include data collection through observation, interviews, and documentation, which are then analyzed using the Miles, Huberman, and Saldana analysis model. The data validity test used source triangulation and technique triangulation techniques. Of The Child Friendly School Program (SRA) at SMP Negeri 15 Yogyakarta has been running well based on four aspects according to Edward III's theory, namely communication, resources, disposition, and bureaucratic structure. 2) The main supporting factors of the implementation of the S6RA Program at SMP Negeri 15 Yogyakarta include a strong commitment from the principal and teachers, continuous training, inclusive facilities, and a participatory decision-making system. The inhibiting factors include inequality in students' understanding of the program, lack of intensity of information delivery, imbalance in the quality of facilities between classes, and less than optimal involvement of parents in program evaluation. Keywords: Implementation, Child Friendly School Program (SRA), SMP Negeri 15 Yogyakarta.